Foundations, Design, and Integration of Customer Relationship Management (CRM) Systems Within Corporate Knowledge Management Strategies - Moser, PhD., Martin A.; Seyr, PhD., Bernhard F. (Journal of Knowledge Management Practice, 2024)
In highly competitive markets, companies need to secure their long-term viability by establishing and maintaining competitive advantages using Customer Relationship Management (CRM) systems. The way these systems are designed significantly impacts a corporation's future growth and profitability and should be recognized as a key factor in the success of corporate knowledge management. This paper aims to identify the design features and prerequisites of CRM systems that contribute to increased sales, the expansion of corporate knowledge, and overall organizational development. An empirical study conducted in 2019 within the Austrian packaging industry (Moser, 2021) highlights the importance of identifying CRM system requirements that enhance user acceptance. The design criteria identified can guide the implementation of future CRM projects, ensuring proper use and approval, and contribute to the development of a comprehensive CRM strategy that integrates corporate knowledge management.
Keywords: knowledge management; customer relationship management (CRM); competitive advantage; corporate knowledge management; CRM system design